I—Fundamental Powers, Evolved Powers, and Mental Powers. (4th June 2018) - Bird, Alexander
Abstract: Powers have in recent years become a central component of many philosophers' ontology of properties. While I have argued that powers exist at the fundamental level of properties, many other theorists of powers hold that there are also non-fundamental powers. In this paper I articulate my reasons for being sceptical about the existing reasons for holding that there are non-fundamental powers. However, I also want to promote a different argument for the existence of a certain class of non-fundamental powers: properties which have natural selection to thank for their existence and nature. Such properties will include functional properties of organisms, and so may also include their mental properties.